2014
DOI: 10.7287/peerj.preprints.563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Definition of sampling units begets conclusions in ecology: the case of habitats for plant communities

Abstract: In ecology, expert knowledge on habitat characteristics is often used to define sampling units such as study sites. Ecologists are especially prone to such approaches when prior sampling frames are not accessible. Here we ask to what extent can different approaches to the definition of sampling units influence the conclusions that are drawn from an ecological study? We do this by comparing a formal versus a subjective definition of sampling units within a study design which is based on well-articulated objecti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…, Mörsdorf et al. ). In our meta‐analysis, the impact of a researcher's expectations on the outcomes of the study is clearly seen from the greatest reported effects for leaves that were sampled by authors only, while an involvement of technicians (who are usually not aware of the hypothesis or have less interest in confirming it) decreased the magnitude of the differences in herbivory between the environments.…”
Section: Discussionmentioning
confidence: 99%
“…, Mörsdorf et al. ). In our meta‐analysis, the impact of a researcher's expectations on the outcomes of the study is clearly seen from the greatest reported effects for leaves that were sampled by authors only, while an involvement of technicians (who are usually not aware of the hypothesis or have less interest in confirming it) decreased the magnitude of the differences in herbivory between the environments.…”
Section: Discussionmentioning
confidence: 99%
“…Functional groups have also shown highly conflicting responses across studies; for example, evergreen shrubs have shown positive, neutral and negative responses to warming (Elmendorf, Henry, Hollister, Björk, Boulanger‐Lapointe, et al, ; Hollister, Webber, & Tweedie, ; Zamin, Bret‐Harte, & Grogan, ). Finally, functional groups have shown inconsistent responses among and within experiments, in different years (Cornelissen & Makoto, ), time‐scales (Saccone & Virtanen, ), environmental conditions (Dorrepaal, ) and spatial scales (Mörsdorf et al, ).…”
Section: Introductionmentioning
confidence: 99%